Computers and commonsence - Hunt, Roger; Shelley, John. (Englewood Cliffs, N.J. : Prentice Hall, 1983)
This book is written in order to provide a general guide to basic computing concepts for a growing population who found it necessary to come to terms with the computer.
Includes bibliographical references and index.
rpm 23/01/2019
Loans
Keywords: Computers; Electronic digital computers